PENGARUH DIMENSI KEPERCAYAAN (TRUST) TERHADAP PARTISIPASI (PARTICIPATION) PELANGGAN WULAN RENT CAR - Dian Novita; Septian Wulandari (UNIVERSITAS INDRAPRASTA PGRI, 2020)
The aims of this study is the level of customer participation in terms of the dimensions of trust to participation Rental Rental Services on Wulan Car Rental Customers. If there is a positive significant relationship, then there is a large influence trust in the participation of rental service customers. The research method is a survey with interaction and regression analysis techniques to determine the relationship between variables. The sample used as the object of research was 75 customers who used rental services in the Wulan rent car. The meeting was conducted by asking for a questionnaire from the Wulan rent customers. The instrument contains indicators of trust dimensions, there are capability, virtue, and integrity, as well as participation which are elaborated on questions that meet the Likert Scale. Validity test by using the product moment inspection technique with the result that all items of the questionnaire have a corrected value of the total correction item of more than r-table of 0.1914 so that 13 items of the questionnaire are suitable for use in research instruments. Reliability test using the value of Conbarch's alpha is 0.896. It means that 13 items of questionnaire are good categorized and can be a criterion in the research instrument. The conclusion is related to the variables of ability, virtue, and integrity that are significant to the participation of rental services in the Wulan rent car, there is no significant effect on the ability and benevolence of the variables on the participation of rental services in the rental car. There is a significant integrity variable to the participation of the car rental in wulan car rental, and the most dominant variable of this study is integrity with t-value of 3.203.